Morphologic changes in the model tintinnid Schmidingerella (Alveolata, Ciliophora) during the cell cycle, including the first volumetric analyses of the lorica-forming material - Sabine Agatha; Birgit Weißenbacher; Laura Böll; Maximilian H. Ganser (BMC Microbiology)
Abstract Background Tintinnids are marine planktonic ciliates with tube-shaped or vase-shaped loricae (shells). During the cell cycle, lorica-forming material (LFM) is generated and accumulates in the proter (anterior division product). After transverse fission, the proter leaves the lorica and subsequently secretes the material, creating its own shell, while the opisthe (posterior division product) retains the parental one. The timing of material production and its final quantity are unknown. Results Our study focussed on Schmidingerella Agatha & Strüder-Kypke, 2012, a model tintinnid genus with transparent, champagne flute-shaped loricae. Protargol-stained field material from the Chesapeake Bay on the Northwest Atlantic provided detailed insights into the morphologic changes, including the LFM production, during the cell cycle. We defined five division stages based on features of the opisthe’s newly forming membranellar zone (oral primordium) recognisable both in live and fixed material. The start of LFM production in middle dividers and its intracellular distribution matched the findings obtained from monoclonal, methyl blue-eosin-stained culture material from the Northeast Pacific, in which the LFM was volumetrically analysed. Just before fission, the LFM occupied on average 6.7% of the cell volume. The wall volume of the finished lorica estimated by a shape function was at least 4.5-fold larger than the volume of the intracellular material. Conclusions The LFM is generated only during a certain period of the cell cycle, i.e., in early middle to late dividers. The difference in volume between the initially secreted LFM and the finished lorica wall suggests that significant structural changes take place in the material during lorica formation.